Effect of ensiling a total mixed ration on feed quality for cattle in smallholder dairy farms = Efecto de ensilar una ración totalmente mezclada sobre la calidad nutritional para el ganado en pequeñas explotaciones lecheras - Bretschneider, Gustavo (2015)
The aim of this study was to assess the impact of ensiling a total mixed ration (TMR) on chemical composition, fermentation and sensory characteristics. Whole-plant corn (WPC) was ensiled alone, as a control, or in combination with other available local feeds. Ensiled feedstuffs were manually mixed and packed into mini-silos. Thereafter, they were stored and allowed to ferment for 75 days. Mould growth was not observed. Color was scored as good for both silage treatments, whereas odor was scored as moderate for TMR silage and good for WPC silage. The pattern and rate of decrease of pH during the storage was not different between silage treatments. However, mean pH values were different (P < 0.01; 3.81 vs. 4.38) between WPC- and TMR-silages, respectively. Relative to WPC silage, the concentration of dry matter (DM) (36.58 vs. 64.25 %; P = 0.001), crude protein (9.89 vs. 18.15 %; P = 0.005) and metabolizable energy (P = 0.03; 2.51 vs. 2.80 Mcal/kg DM) was higher for TMR silage, as expected. Furthermore, the neutral detergent fibre content decreased along the storage but at a different rate (P = 0.04) for each silage treatment. The rate of decrease, expressed as percentage/day, was -0.16 and -0.05 for WPC- and TMR- silage, respectively. Overall, TMR silage had adequate attributes to cope with dairy cow requirements. It is suggested that the ensiling of TMR, composed by locally available feedstuffs, is a simple and low cost technology that could aid smallholder dairy to improve their net daily income.